Developmental Differences of Structural Connectivity and Effective Connectivity in Semantic Judgments of Chinese Characters - Fan, Li-Ying; Lo, Yu-Chun; Hsu, Yung-Chin; Chen, Yu-Jen; Tseng, Wen-Yih Isaac; Chou, Tai-Li (Frontiers in Human Neuroscience, 2020)
Previous studies have investigated the developmental differences of semantic processing regarding brain activation between adults and children. However, it is little known whether the patterns of structural connectivity and effective connectivity differ between adults and children during semantic processing. Functional magnetic resonance imaging (fMRI), diffusion spectrum imaging (DSI), and dynamic causal modelling (DCM) were used to study the developmental differences of brain activation, structural connectivity, and effective connectivity during semantic judgments. Twenty-six children (8- to 12-year-olds) and twenty-six adults were asked to indicate if character pairs were related in meaning. Compared to children, adults showed greater activation in the left ventral inferior frontal gyrus (IFG) and left middle temporal gyrus (MTG). In addition, adults had significantly greater structural connectivity in the left ventral pathway (inferior frontal occipital fasciculus, IFOF) than children. Moreover, adults showed significantly stronger bottom-up effect from left fusiform gyrus (FG) to ventral IFG than children in the related condition. In conclusion, our findings suggest that age-related increases in brain activation (ventral IFG and MTG), structural connectivity (IFOF), and effective connectivity (from FG to ventral IFG) might be associated with the bottom-up influence of orthographic representations on retrieving semantic representations for processing Chinese characters.